The Impact of Leadership Style on Civil Servants Work Behavior - Harbu Hakim; Masdar Mas’ud; Muhammad Syafi’i Basalamah; Junaidi Zakaria; Zaenal Arifin Sahabuddin (Enrichment : Journal of Management, 2023)
Leadership plays an important role in determining the success of an organization in surviving the direct impact of the Covid-19 pandemic. However, an effective leadership model for sustainable performance success during this pandemic is still an issue of serious debate among both management practitioners and experts, and has become a central issue in theoretical studies and empirical research in the last few decades. This study aims to examine the effect of leadership models (transformational and transactional leadership) and work motivation on individual performance and job satisfaction. This research involved the State Civil Apparatus (ASN) working in South Sulawesi. Given the Covid-19 pandemic, data collection techniques were carried out via an electronic questionnaire, which was measured using a Likert scale of 1–5. To test the primary data and analyze the relationship between variables in the structural model that was built, covariance-based Structural Equation Modeling (SEM) or AMOS (SEM-AMOS) was used. The results of the research are expected to contribute to the local government's strategy in increasing the motivation, performance and satisfaction of ASN so that they can cope with the Covid-19 pandemic in South Sulawesi.